Таня Гроттер и ботинки кентавра: [повесть] / Дмитрий Емец - Емец Дмитрий Александрович (Тана Гроттер, 2005)
Экземпляры: 5 (20190703) / Инвентарный номер: 43969 / Цена: 110.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Е 60 / ББК: 84(2Рос=Рус)6